Campur Kode dalam Media Sosial Tiktok: Sebuah Studi Gaya Bahasa dan Dampaknya - Sihombing, Nirvana; Arfanti, Yulia (Melati Institute, 2024)
The purpose of this research is to analyze the use of code mix in TikTok content, identify the types of code mix used, and find out the impact of the use of code mix on online communication.The research method used is descriptive qualitative method. The data was obtained from TikTok content containing code mixes in Indonesian and other languages.The data collection technique used is documentation technique and the data analysis technique includes data presentation and conclusion drawing.The findings show that various types of code mixes are used in TikTok content: inward code mix, outward code mix, and mixed code mix.The forms of code mix found include words, phrases, clauses, and idioms.The use of code mix in TikTok content has several functions, including expressing emotions, showing identity, and creating familiarity. However, excessive use of code-mixing can affect online communication, making messages difficult to understand, reducing the clarity of information, and reducing communication effectiveness.